2015
DOI: 10.1021/acs.molpharmaceut.5b00035
|View full text |Cite
|
Sign up to set email alerts
|

Phagocytosed Clofazimine Biocrystals Can Modulate Innate Immune Signaling by Inhibiting TNFα and Boosting IL-1RA Secretion

Abstract: Clofazimine (CFZ) is an FDA-approved leprostatic and anti-inflammatory drug that massively accumulates in macrophages, forming insoluble, intracellular crystal-like drug inclusions (CLDIs) during long-term oral dosing. Interestingly, when added to cells in vitro, soluble CFZ is cytotoxic because it depolarizes mitochondria and induces apoptosis. Accordingly, we hypothesized that in vivo, macrophages detoxify CFZ by sequestering it in CLDIs. To test this hypothesis, CLDIs of CFZ-treated mice were biochemically … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
55
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
2

Relationship

5
4

Authors

Journals

citations
Cited by 45 publications
(57 citation statements)
references
References 65 publications
(149 reference statements)
2
55
0
Order By: Relevance
“…CLDIs were isolated from the spleen of 8 week CFZ fed mice using a previously described method [21]. In brief, the spleens were homogenized with a syringe plunger and then filtered through a 40 μm cell strainer to remove connective tissue debris.…”
Section: Isolation Of Spleen Cldismentioning
confidence: 99%
See 1 more Smart Citation
“…CLDIs were isolated from the spleen of 8 week CFZ fed mice using a previously described method [21]. In brief, the spleens were homogenized with a syringe plunger and then filtered through a 40 μm cell strainer to remove connective tissue debris.…”
Section: Isolation Of Spleen Cldismentioning
confidence: 99%
“…Based off of previous work, it has been shown that CLDIs tend to be found within tissue macrophages, such as Kupffer cells of the liver, red pulp macrophages of the spleen, and alveolar macrophages within the lung [18,28,29]. Due to the extensive accumulation within alveolar macrophages, these cells were chosen to test this multi-parameter imaging and analysis system in live cells.…”
Section: Multi-parameter Live Cell Imaging and Quantification Of Diatmentioning
confidence: 99%
“…Furthermore, in vitro studies have shown that intracellular CFZ biocrystals dampen proinflammatory pathways while enhancing anti-inflammatory signals (23).…”
mentioning
confidence: 99%
“…IL1ra-deficient mice exhibit excessive inflammation when bred to various disease models, and patients with IL1RA deficiency show severe inflammatory conditions (14)(15)(16)(17)(18)(19). The icIL1RA isoforms are considered a reservoir of biologic active IL1RA, but the factors that regulate the release of icIL1RA have not been studied in detail (6,(20)(21)(22)(23).…”
Section: Introductionmentioning
confidence: 99%